Molecular characterization of the plastidic glucose-6-phosphate dehydrogenase from potato in comparison to its cytosolic counterpart. - von Schaewen, A (1995)
We report on the cloning of a plastidic glucose-6-phosphate dehydrogenase (EC 1.1.1.49) from higher plants. The complete sequence of the plastidic enzyme was obtained after rapid amplification of cDNA ends and comprises a putative plastidic transit peptide. Sequences amplified from leaf or root poly(A+) RNA are identical. In contrast to the cytosolic enzyme, the plastidic isoform is subject to redox modulation, i.e. thioredoxin-mediated inactivation by light. But when the plastidic enzyme is compared to a cyanobacterial homolog, none of the cysteine residues is conserved. The recombinant enzyme was used to raise antibodies in rabbits. Gene expression was studied in potato (Solanum tuberosum L.), at both the RNA and protein levels, revealing different patterns for the isoforms. The gene encoding the cytosolic enzyme was transcribed in all tissues tested, and the highest transcription was detected in tubers. In contrast, expression of the gene encoding the plastidic enzyme was confined to green tissues. Wounding of leaves resulted in a slight increase in the expression of the gene encoding the cytosolic isoform and a shutdown of the plastidic counterpart. Compared to the situation in soil, elevated transcription of the gene encoding the plastidic enzyme is found in roots of hydroponically grown potato plants, which is in agreement with the postulated role for this isoform in nitrite reduction.